Ficus deltoidea suppresses endothelial activation, inflammation, monocytes adhesion and oxidative stress via NF-κB and eNOS pathways in stimulated human coronary artery endothelial cells - Amirah Mohd Ariff; Nurul Ain Abu Bakar; Suhaila Abd. Muid; Effat Omar; Nor Hadiani Ismail; Abdul Manaf Ali; Noor Alicezah Mohd Kasim; Hapizah Mohd Nawawi (BMC, 2020)
Abstract Background Ficus deltoidea (FD) has been shown to have antidiabetic, anti-inflammatory, antinociceptive and antioxidant properties. However, its effects on key events in the pathogenesis of atherosclerosis are unknown. Aim To investigate the endothelial activation, inflammation, monocyte-endothelial cell binding and oxidative stress effects of four FD varieties. Methods Human coronary artery endothelial cells (HCAEC) were incubated with different concentrations of aqueous ethanolic extracts of FD var. trengganuensis (FDT), var. kunstleri (FDK), var. deltoidea (FDD) and var. intermedia (FDI), together with LPS. Protein and gene expression of vascular cell adhesion molecule-1 (VCAM-1), intercellular cell adhesion molecule-1 (ICAM-1), endothelial-leukocyte adhesion molecule-1 (E-selectin), interleukin-6 (IL-6), Nuclear factor-κB (NF-κB) p50 and p65 and endothelial nitric oxide synthase (eNOS) were measured using ELISA and QuantiGene plex, respectively. Adhesion of monocyte to HCAEC and formation of reactive oxygen species (ROS) were detected by Rose Bengal staining and 2'-7'-dichlorofluorescein diacetate (DCFH-DA) assay. Results FDK exhibited the highest inhibition of biomarkers in relation to endothelial activation and inflammation, second in reducing monocyte binding (17.3%) compared to other varieties. FDK (25.6%) was also the most potent at decreasing ROS production. Conclusion FD has anti-atherogenic effects, possibly mediated by NF-κB and eNOS pathways; with FDK being the most potent variety. It is potentially beneficial in mitigating atherogenesis.